AN EXPLORATION INTO THE INFLUENCE OF DIGITAL POP-UPS ON QUALITY OF LIFE - Diepenbroek, Tayla Jane (The IIE, 2019)
This research aimed to explore whether the implementation of the digital library in the informal settlement of Vastfontein has increased the literacy levels of the community and provided them with greater opportunities to improve their quality of life. Hence, the purpose of this research was to explore the influence that digital pop-ups have on quality of life in rural communities. This research used an exploratory research design, an interpretivism research paradigm and a qualitative research approach. Therefore, a non-probability sampling method was used, which was purposive sampling. This technique was relevant to this study as the research question was specifically concerned with the people who make regular use of the digital library and those people who specifically make use of the digital library for the purpose of learning and gaining information and literacy skills. The research uses a neighbourhood revitalisation (Habitat, 2018) and quality of life framework that is substantiated by Maslow’s hierarchy of needs (2007) pyramid as a benchmark to access potential changes in quality of life. The data collection method that was used in this research was semi-structured, in-depth interviews and then analysed using a thematic analysis in order to subjectively explore the influence of the digital library on the quality of life of the people living in the Vastfontein community. The research found that the implementation of the digital pop-ups in informal settlements have a positive impact on the quality of life of those people living in the community.
Keywords: Brand; Digital literacy; Brand management; Digital library; Quality of life; Informal settlements